Perancangan Sistem Inventori Barang Berbasis Web Dengan Metode Waterfall Pada Namaaz Dining Restoran - Gusnanto .; Eko Suharyanto (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The development of information technology currently plays a vital role in supporting business operational efficiency, including in the culinary industry sector which has a high level of complexity. Namaaz Dining, as the first molecular gastronomy restaurant in Indonesia, applies a unique concept where the presentation theme and food menu change completely every year. This seasonal or annual concept change results in a massive and diverse accumulation of cooking utensils, serving plates, and decorative props in the storage warehouse. Currently, the inventory management process at Namaaz Dining is still carried out conventionally and relies heavily on the memory capability (tacit knowledge) of warehouse employees without an integrated recording system. This condition causes various serious operational problems, including difficulty in tracking item storage locations, inaccuracy of physical stock data compared to manual records, and inefficiency of time and energy when staff must dismantle the warehouse to search for old properties to be reused. This study aims to design and build a web-based item inventory information system to overcome these asset management problems. The software development method applied is the System Development Life Cycle (SDLC) Waterfall model, which is carried out systematically starting from the stages of system requirements analysis, design, program code implementation, system verification, to maintenance. Data collection techniques were carried out through direct observation methods of the workflow in the warehouse and in-depth interviews with restaurant management. The final result of this research is a web-based inventory application capable of recording incoming and outgoing item transactions, monitoring stock availability in real-time, and providing accurate item location search features. The implementation of this system is expected to improve work operational efficiency, minimize the risk of company asset loss due to human error, and assist Namaaz Dining management in strategic decision-making regarding the reuse of inventory assets for the next menu season.